Perception of PGSD FKIP UPR Students on the Independent Campus Learning Program - Nyoto, Nyoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Higher Education curriculum must be in line with the demands of the World of Work and the Industrial World so that its graduates can be well absorbed by both of them, with that Minister of Education Nadiem Makarim made a new breakthrough for educational change by creating an Independent Campus Learning Program (MBKM) at PT which consists of eight programs, namely student exchange, internship/industrial practice, teaching assistance in education units, research/research, humanitarian projects, entrepreneurship, independent studies/projects and building village/college thematic real work. This study uses a qualitative descriptive approach with online questionnaire distribution techniques via google form and online interviews through Gmeet. The research analysis uses Miles & Hubermen analysis, namely data reduction, display data and draw data conclusions. Respondents who filled out the questionnaire were 87 respondents while those interviewed were 8 students from semester 5 and semester 7. The results showed that the majority of students knew about the MBKM program whose information was mostly obtained from social media, namely WhatsApp groups, YouTube and Instagram and some students received information from friends, banners and lecturers. Students who take courses outside the study program on campus and outside the UPR campus have one student each, namely class management and research methodology courses. Most of the students have not participated in internship programs, teaching assistance in education units, research/research, humanitarian projects, entrepreneurship, independent study/project but most of the students have done village building programs/Thematic Community Service Program. Of the eight MBKM programs, most students agree with the existing programs.